Antiseptics: analysis of assortment, technologies of compounding and using - O. Yu. Toziuk; O. V. Kryvoviaz; Yu. O. Tomashevska; A. S. Voronkina; H. I. Kramar; V. V. Kudria; M. T. Lesko (Фармацевтичний журнал, 2022)
Proper hand hygiene disrupts the spread of a numerous infections and is therefore a guarantee of good human health. Wide use of antiseptics by the public raises questions about their effectiveness, safety and availability. At the same time, the culture of hand hygiene is a priority for all spheres of society.